Central Giant Cell Tumour-A Case Series - Balaji V M; Pankaja Gupta; Nini George; Smile Singla; Swathy Sridhar (RGUHS Journal of Medical Sciences)
Central giant cell granuloma CGCG is a benign expansile osteolytic lesion of the jawbone. Previously termed a central giant cell CGC reparative granuloma it is now more accurately classified as a CGC tumor as it represents a benign neoplasm of osteoclast precursors. Surgery is the standard course of treatment for CGCG. On the other hand morbidity is linked to surgical care. Conservative treatment modalities such as interferon alpha therapy calcitonin therapy and intralesional corticosteroid injections can significantly reduce postoperative morbidity however it is important to follow up on these cases for an extended period in order to study the effects and potential recurrence of these cases. Three CGC tumour cases are presented in this case series.